Factors that Influence Take Up of an Institutional VLE by Individual Lecturers Preliminary Findings - Traxler, John (Proceedings of the International Conference on Networked Learning, 2002)
This paper reviews progress on a project investigating the roll out of an institutional VLE at the University of Wolverhampton. The paper concentrates on some of the social, cultural and institutional aspects of a complex and incomplete process. It discusses the framework within which individual lecturers make decisions about the nature and extent of their engagement with the VLE and rehearses some of the methodological concerns involved in trying to elucidate these decisions. This paper represents a snapshot of investigative work near its mid-point.